Cancer in Anti‐Neutrophil Cytoplasm Antibody‐Associated Vasculitis and Polyarteritis Nodosa in Australia: A Population‐Based Study. Issue 3 (7th December 2021) - Tieu, Joanna; Lester, Susan; Raymond, Warren; Keen, Helen; Hill, Catherine L.; Nossent, Johannes
Abstract : Objective: The study objective was to compare incident cancer rates among patients with anti‐neutrophil cytoplasm antibody‐associated vasculitis (AAV) and polyarteritis nodosa (PAN) in Western Australia (WA) with the general population and perform time‐varying analyses to identify periods with greatest excess cancers. Methods: Administrative health data from patients hospitalized with incident AAV/PAN from 1980 to 2014 were linked to the WA cancer registry, which holds compulsorily reported cancer data (excluding skin squamous cell and basal cell carcinomas). Incident cancer rates in patients with AAV/PAN were compared with age‐, sex‐, and calendar‐year‐matched WA population rates. Results: Patients with AAV/PAN had higher overall rates of incident cancer compared with the matched population (standardized incidence ratio [SIR], 1.74; 95% confidence interval [CI], 1.42‐2.10). In subgroup analyses, incident cancer rates in patients with granulomatosis with polyangiitis/eosinophilic granulomatosis with polyangiitis were approximately double the general population (SIR, 2.21; 95% CI, 1.73‐2.78) but similar to the general population in patients with microscopic polyangiitis/PAN (SIR, 1.21; 95% CI, 0.85‐1.68). Patients with AAV/PAN had higher rates of genitourinary, skin, hematological, and lung cancers. Excess rates of hematological and lung cancers peaked early after diagnosis, whereas excess skin and genitourinary cancer rates peaked at 5 and 10 years, respectively. Conclusion: This study highlights the importance of long‐term cancer surveillance in patients with AAV/PAN and defines time frames of excess risk for specific cancers, which may help inform guidance on cancer screening. Furthermore, it indicates the need for skin surveillance for melanoma in addition to nonmelanoma skin cancers in patients who have greater environmental ultraviolet exposure, such as in Australia.